Immune checkpoint inhibitors and tuberculosis: an old disease in a new context. Issue 1 (January 2020) - Langan, Ewan A; Graetz, Victoria; Allerheiligen, Judith; Zillikens, Detlef; Rupp, Jan; Terheyden, Patrick
Summary: Tuberculosis, the leading cause of infection-related death in developing regions, is a leading cause of morbidity and mortality worldwide. Screening for, and treatment of, latent Mycobacterium tuberculosis infection is routine before initiation of anti-tumour necrosis factor α (anti-TNFα) agents in the management of psoriasis, Crohn's disease, and rheumatoid arthritis. By contrast, screening for latent tuberculosis before immune checkpoint inhibitor treatment in cancer is not routine, despite the increasing number of reports of primary infection with M tuberculosis or reactivation of latent M tuberculosis infection during such treatment. We present our experience with M tuberculosis screening in 70 patients who underwent immune checkpoint inhibitor therapy for metastatic skin cancer. Based on our understanding of the interaction between M tuberculosis and the immune system, we present the argument for tuberculosis screening before immune checkpoint inhibitor therapy and its use when considering anti-TNFα treatment for severe immune-related adverse events. We call for increased vigilance during immune checkpoint inhibition until its effects on tuberculosis pathophysiology are fully ascertained.